Historical processes of urban form and land-use change at Shwedagon Pagoda’s surrounding area in Yangon, Myanmar - Hirano, Kuniomi; Yokohari, Makoto (International Planning History Society Proceedings, 2018)
Shwedagon Pagoda is located at the centre of Yangon, Myanmar. It is one of the nation’s most respected religious monuments. The objective of this research was to identify the details of the historical processes of urban form and land-use change in the area surrounding the pagoda in relation to political regime transition. This research also focused on the evolving processes of the pagoda festival and its land use in the surrounding area; the festival is a typical occasion during which the relationship between the pagoda and the surrounding area is prominently visible. An interview survey, newspaper review survey, field survey, mapping work, and literature review were conducted to accomplish this research’s goals. The pagoda’s land property and the land use of the surrounding area have undergone significant changes. This research identified the historical processes through which temporary, multi-purpose open spaces in the area surrounding the pagoda have been divided, fixed for individual land uses, and segmentalized according to role during the pagoda festival. For example, this includes markets and stalls that have been altered for use as permanent shops and restaurants, entertainment and amusement facilities that were enclosed in parks, and smaller forms of lodging that have become hotels.